2011
DOI: 10.1111/j.1440-1827.2011.02725.x
|View full text |Cite
|
Sign up to set email alerts
|

A polygene network model for the complex pathological phenotypes of collagen disease

Abstract: Almost 70 years after the description of 'collagen disease' by P. Klemperer et al., it is still controversial whether the diversity and similarity of pathological manifestations among the collagen diseases depends on ambiguity in diagnosis or is an intrinsic quality of the collagen diseases themselves. A genome wide analysis of the MRL mouse models of collagen disease may shed some light on the complex pathological manifestations. Study of the susceptibility loci to each type ofcollagen disease (such as glomer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Interestingly, MRL and AKR, both of which develop autoimmune disease in the presence of Fas lpr , carry CD72 c , whereas most of the other strains of mice, including BALB/c and C57BL/6 (B6), carry either CD72 a or CD72 b (18,19). Moreover, studies using microsatellite markers revealed association of the loci containing Cd72 to development of glomerulonephritis in MRL/lpr mice (20)(21)(22) …”
mentioning
confidence: 99%
“…Interestingly, MRL and AKR, both of which develop autoimmune disease in the presence of Fas lpr , carry CD72 c , whereas most of the other strains of mice, including BALB/c and C57BL/6 (B6), carry either CD72 a or CD72 b (18,19). Moreover, studies using microsatellite markers revealed association of the loci containing Cd72 to development of glomerulonephritis in MRL/lpr mice (20)(21)(22) …”
mentioning
confidence: 99%
“…For example, we found that IFN-inducing antivirus proteins such as Ifit2, Ifit3, Mx2, and ApoL9b were downregulated in activated GOLPH2 KO BMDCs, which indicates that GOLPH2 may play a positive role in host resistance to viral infections. Abnormal expression of collagen proteins could lead to collagen diseases, which are a heterogeneous group of systemic inflammatory diseases of autoimmune origin that affect a wide range of organs and systems, including systemic lupus erythematosus and rheumatoid arthritis (48,49). We found that col1a2, col3a1, col5a2, and col8a1 were upregulated in resting GOLPH2 KO cells, suggesting the potential involvement of GOLPH2 in the pathogenesis of these autoimmune diseases (Supplemental Fig.…”
Section: Discussionmentioning
confidence: 77%
“…An additional factor that influences the mechanical properties of soft connective tissues is genetic variation between individuals . For example, polyallelic variation in collagen necessarily results in variations in the mechanical properties of connective tissues between individuals , and thus the load threshold of bruising may vary somewhat from subject to subject due to amino acid sequence differences in the protein. A final recommendation for future studies investigating capillary failure and bruising would be the evaluation of loading rate, as well as determining load and pressure thresholds.…”
Section: Discussionmentioning
confidence: 99%